A proposal of total productive maintenance training system - Yuniawan, Dani; Ito, Teruaki; Mohamad, Effendi (2013)
The objective of this research is to propose a Total Productive Maintenance Training System (TPMTS),which is integrated with user training program (UTP) in order to advance the user awareness regarding the Total Productive Maintenance (TPM) concept. The TPMTS itself provide the integration of e-learning module, simulation module and experiment module.The simulation module is employing simulation model by using Arena simulation software. While the experiment module employing Taguchi experiment design method. With these integration modules, not only the user's awareness about TPM, however TPMTS can also recognize the production line characteristic through Overall Equipment Effectiveness (OEE) score measurement. The TPMTS itself is a training system targeted to increase user's comprehension and their confidence levels towards TPM concept.